ENDOVASCULAR TREATMENT OF SUPERIOR VENA CAVA SYNDROME : A SYSTEMATIC REVIEW - Atin, Fulgensius; Prasetyanto, R. Dhany; Johana Tiluata, Leonora; Alexander, Nick; Valerie Gunawan, Alyssa Claudia; Kurniawan Sudargo, Giovanni (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Endovascular stenting has been used to manage superior vena cava syndrome for several decades and has become standard firstline practice. Superior vena cava (SVC) syndrome is caused by the obstruction of the SVC and can result in significant morbidity and mortality. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of cthe requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 292 articles, whereas the results of our search on SagePub brought up 315 articles. The results of the search conducted for the last year of 2013 yielded a total 163 articles for PubMed and 127 articles for SagePub. In the end, we compiled a total of  6 papers, 4 of which came from PubMed and 2 of which came from SagePub. We included six research that met the criteria. Conclusion: In summary, this review confirms the effectiveness of endovascular stenting in managing SVCS. Further directions of research may include specific outcomes of endovascular stenting in benign SVCS, and the impact of procedural characteristics, such as the use of anticoagulation and type of stent used, on outcomes.